2016
DOI: 10.1111/jon.12356
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Studies of a Kidney Safe Iodinated Contrast Agent

Abstract: BACKGROUND AND PURPOSEContrast‐induced acute kidney injury (CI‐AKI) is a serious complication of the use of iodinated contrast agents. This problem is particularly acute in interventional neurology and interventional cardiology, probably due to the intra‐arterial route of injection, high contrast volumes, and preexisting risk factors of these patients. In an attempt to develop a contrast agent that is less damaging to the kidneys, we have studied the effects of adding a small amount of the substituted cyclodex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…In that research, it was concluded from the results that a nonionic radiocontrast such as Iohexol cause acute renal failure 58 . In another study in 2016, acute kidney injury of Iohexol was considered and using a new complex consisted of sulfobutyl-ether-β-cyclodextrin (SBECD) and Iohexol, the toxicity decreased from 50% to 12% in a rodent model compared to the Iohexol alone 59 . Hence, it is of great importance to find an alternative to the conventional radiocontrast agents.…”
Section: Discussionmentioning
confidence: 99%
“…In that research, it was concluded from the results that a nonionic radiocontrast such as Iohexol cause acute renal failure 58 . In another study in 2016, acute kidney injury of Iohexol was considered and using a new complex consisted of sulfobutyl-ether-β-cyclodextrin (SBECD) and Iohexol, the toxicity decreased from 50% to 12% in a rodent model compared to the Iohexol alone 59 . Hence, it is of great importance to find an alternative to the conventional radiocontrast agents.…”
Section: Discussionmentioning
confidence: 99%
“…Although the currently available contrast agents are considered to be safe, their use is not completely without risk [ 4 ] and considerable attention has been focused on allergic reactions, physiologic reactions, nephrotoxicity, nephrogenic systemic fibrosis, and gadolinium deposition in tissues. [ 4 , 5 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…SBECD is widely used in marketed drug formulations to increase solubility, including remdesivir, one of the few approved treatments for Covid‐19 37 . However, in our studies, only one molecule of SBECD per 40 molecules of iohexol is necessary for nephroprotection, ruling out a solubilization mechanism in this case 36 …”
Section: Introductionmentioning
confidence: 60%
“…As we previously reported in this journal, SBECD (trade name Captisol, Ligand Pharmaceuticals, Inc, San Diego, CA) was shown to mitigate CI‐AKI in laboratory animals 36 . A reformulation of iohexol with SBECD is now in phase II clinical trials in the United States, for prevention of CI‐AKI in vulnerable patients undergoing elective coronary angiography.…”
Section: Introductionmentioning
confidence: 92%